Operações de crédito: um estudo de caso sobre financiamentos para os setores rural, comercial e industrial - Miranda Filho, Francisco Tavares de (2008)
This case study aims to investigate the effects of usury and compound interest in the process of acquiring bank debt. The sample was made up of sixty (60) credit transactions, initiated from 1994-2003, all of which are in default and awaiting judicial rulings in the district court of Parnaíba. A brief analysis of the historical, judicial and politico-economical aspects of credit in Brazil relating to the rural, commercial and industrial sectors is included with emphasis given to the legal aspects of debt collection and economic status. As methodology, a field study was undertaken, achieved with the sixty (60) borrowers during their judgment in order to assist the evaluation of the effects of usury and compound interest in the evolution of the debts. The conclusion reached is that usury and compound interest application were factors that contributed to the debt arriving at the point of default. It should be emphasized, however, that the power of said result does not extend to any and all type of credit transaction.